Birds and flowers in Tennyson's poetry - Goodwin, William H. (My University, 1905)
Introduction: In the following quotations no special system of classification has been adopted and all the quotations, which the subject includes, have been taken without especial regard to beauty of language or thought. The numbers of the volumes are given in the center of the page Roman numerals and also the title of the poem from which the quotation is taken, while the references are given immediately after the quotation. The references are given for the “Riverside Press Edition” which is published by “Houghton Mifflin & Co. To a lover of nature nothing is more interesting than its study either in books or as you observe it. Anyone who may become interested enough, to read these quotations, will find them, I trust both pleasing and instructive and so I leave you to judge, hoping that you gain as much from their perusal as he, who has selected them.
Citation: Goodwin, William H. Birds and flowers in Tennyson's poetry. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Theses; Manuscripts (documents)